How much conversation content is actually social: human conversational behaviour revisited - Anna Szala; Sławomir Wacewicz; Marek Placiński; Aleksandra Ewa Poniewierska; Arkadiusz Schmeichel; Michal Mikolaj Stefanczyk; Przemysław Żywiczyński; Robin I.M. Dunbar (Language and Cognition)
Our study explores aspects of human conversation within the framework of evolutionary psychology, focusing on the proportion of ‘social’ to ‘non-social’ content in casual conversation. Building upon the seminal study by Dunbar et al. (1997, Human Nature, 8, 231–246), which posited that two-thirds of conversation gravitates around social matters, our findings indicate an even larger portion, approximately 85% being of a social nature. Additionally, we provide a nuanced categorisation of ‘social’ rooted in the principles of evolutionary psychology. Similarly to Dunbar et al.’s findings, our results support theories of human evolution that highlight the importance of social interactions and information exchange and the importance of the exchange of social information in human interactions across various contexts.